High prices attract clove producers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Zanzibar State Trading Corporation raised their price for cloves in September 2001. Grade A cloves now fetches TSH 2,500 shillings per kilo, compared to 1,500 before. Other grades can be sold at higher prices to ZSTC, which the government...